2017
DOI: 10.1093/ptj/pzx055
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain: Investigation of Biases in Outpatient Canadian Physical Therapy

Abstract: There appears to be an implicit professional bias in relation to patients' insurance status; the resulting inequity in service provision highlights the need for further research as a basis for national guidelines to promote equity in access to and provision of quality physical therapy services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Recruitment. Considering that response rates of physiotherapists to online surveys range from approximately 9% (Laliberté et al, 2017) Respondents were excluded from the study if they (a) reported working exclusively in neurological, cardiorespiratory, or paediatric rehabilitation; or (b) failed to meet any of the inclusion criteria described above.…”
Section: Methodsmentioning
confidence: 99%
“…Recruitment. Considering that response rates of physiotherapists to online surveys range from approximately 9% (Laliberté et al, 2017) Respondents were excluded from the study if they (a) reported working exclusively in neurological, cardiorespiratory, or paediatric rehabilitation; or (b) failed to meet any of the inclusion criteria described above.…”
Section: Methodsmentioning
confidence: 99%
“…Regions with a greater number of independent MRI sites had higher rates of early MRI due to potential clinician 'self-referral' [33]. Evidence from simulated scenarios demonstrated private clinicians are more likely to see workers with LBP more often if their healthcare was funded by an income support system (an employer liability system) than by private insurance or out of their own pocket [56]. In clinical scenarios, physiotherapists treat compensated patients similarly to other patients, but were more likely to suggest ongoing physiotherapy for treatment [57].…”
Section: Cmo Configuration 1 (N=3 Pieces Of Literature)mentioning
confidence: 99%
“…Prioritization processes may also involve rationing of services, that is denying access to patients based on specified eligibility criteria [10]. Not surprisingly, prioritization processes and limited access to healthcare services raise issues regarding equity in access [7,[11][12][13][14][15]. These issues are challenging for clinicians, managers and decision makers, knowing that "in a resource-constrained system, giving additional weight to something or someone implies that something or someone else will lose out."…”
Section: Introductionmentioning
confidence: 99%